Opioid Prescribing for Proximal Row Carpectomy versus Four-Corner Arthrodesis - Moran, Thomas E.; Akinleye, Sheriff D.; Demers, Alex J.; Forster, Grace L.; DeGeorge, Brent R., Jr. (Journal of Wrist Surgery, 2021)
Background Proximal row carpectomy (PRC) and four-corner arthrodesis (4-CA) represent motion-sparing procedures for addressing degenerative wrist pathologies. While both procedures demonstrate comparable functional outcomes, postoperative pain presents a surgical challenge that often necessitates the use of opioids.Objectives The aim of this study was to (1) compare opioid prescribing patterns surrounding PRC and 4-CA, (2) identify risk factors predisposing patients to increased perioperative and prolonged postoperative opioids, and (3) examine the association between opioids and perioperative health care utilization.Patients and Methods PearlDiver Patients Records Database was used to retrospectively identify patients undergoing primary PRC and 4-CA between 2010 and 2018. Patient demographics, comorbidities, prescription drug usage, and perioperative health care utilization were evaluated. Perioperative opioid prescriptions and post-operative opioid prescriptions were recorded. Logistic regression analysis evaluated the association of patient risk factors.Results There was no significant difference in perioperative (PRC [odds ratio OR: 0.84, p = 0.788]; 4-CA [OR: 0.75, p = 0.658]) or prolonged postoperative opioid prescriptions (PRC [OR: 0.95, p = 0.927]; 4-CA [OR: 0.99, p = 0.990]) between PRC and 4-CA. Chronic back pain and use of benzodiazepines or anticonvulsants were associated with increased risks of prolonged postoperative opioids. Prolonged postoperative opioids presented increased risks of emergency department visits (OR: 2.09, p = 0.019) and hospital readmissions (OR: 10.2, p = 0.003).Conclusion No significant differences exist in the prescription of opioids for PRC versus 4-CA. Both procedures have high amounts of prolonged postoperative opioid use, which is associated with increased risks of emergency department visits and hospital readmissions.Level of Evidence This is a level III, retrospective comparative study.
Keywords: opioids; narcotics; proximal row carpectomy; four-corner arthrodesis